2015
DOI: 10.1111/jfpp.12514
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of CaCl2 , Peppermint Oil and Salicylic Acid Treatments on Shelf Life Extension of Fresh Mint during Cold Storage

Abstract: Mint is a popular commercially grown refreshing herb with numerous applications. Consumers increasingly require fresh ready-to-eat herbs of good quality. Today, most of the developed methods to control postharvest quality are not practical for industrial applications. The effect of CaCl2 (1 and 2%), peppermint oil (500 and 1,000 mg/L) and salicylic acid (0.5 and 1 mM) on different quality attributes, including chlorophyll, electrolyte leakage, relative water content, proline concentration and overall quality o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…These properties reduce the diffusion of oxygen and increase the accumulation of CO 2 around the fruit surface, leading to reduced water loss and slowing down the activity of enzymes and biochemical reactions that cause pigment synthesis (Perdones et al, 2016). It was reported that the treatment of postharvest min oil (Yousefizad et al, 2015;Owolabi et al, 2021) and thyme oil (Sapper et al, 2019;Cai et al, 2020) reduced respiration rate during storage and extend the postharvest fruit life. Furthermore, the treatment of postharvest peppermint oil (Yousefizad et al, 2015;Owolabi et al, 2021) and thyme oil (Sapper et al, 2019;Cai et al, 2020) reduced respiration rate during storage and extend the postharvest fruit life in fresh fruit.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These properties reduce the diffusion of oxygen and increase the accumulation of CO 2 around the fruit surface, leading to reduced water loss and slowing down the activity of enzymes and biochemical reactions that cause pigment synthesis (Perdones et al, 2016). It was reported that the treatment of postharvest min oil (Yousefizad et al, 2015;Owolabi et al, 2021) and thyme oil (Sapper et al, 2019;Cai et al, 2020) reduced respiration rate during storage and extend the postharvest fruit life. Furthermore, the treatment of postharvest peppermint oil (Yousefizad et al, 2015;Owolabi et al, 2021) and thyme oil (Sapper et al, 2019;Cai et al, 2020) reduced respiration rate during storage and extend the postharvest fruit life in fresh fruit.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that the treatment of postharvest min oil (Yousefizad et al, 2015;Owolabi et al, 2021) and thyme oil (Sapper et al, 2019;Cai et al, 2020) reduced respiration rate during storage and extend the postharvest fruit life. Furthermore, the treatment of postharvest peppermint oil (Yousefizad et al, 2015;Owolabi et al, 2021) and thyme oil (Sapper et al, 2019;Cai et al, 2020) reduced respiration rate during storage and extend the postharvest fruit life in fresh fruit.…”
Section: Discussionmentioning
confidence: 99%